Evaluating Museum Service Experience Through Mobile Ethnography in The Perception of Generation Z - Sirad, Dini Anggraeni (Institut Pariwisata Trisakti, 2019)
A Museum management success factors have changed from previous display of conservation and historical information (Goulding, 1999) towards the integration of positive customer feedback and their perceived experiences of the entire visit. This paper suggests a mobile ethnography as a methodological basis for analyzing Gen Z visitor experience. The method is considered more appropriate as this generation is the first generation born into the world where physical aspects (peoples and places) have digital equivalents where for them the real world and the virtual world naturally overlap (Fairview Capital, 2017). The research used purposive sampling technique that involve Gen Z as the active investigators. The research is conducted in four museums run by the Indonesian government in Jakarta. The result of this research shown critical points in three broad aspects of “Physical and Design